2021
DOI: 10.3390/jcs5060160
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Design of Chitosan-Based Fiber Composite Materials

Abstract: Chitosan composite fibrous materials continue to generate significant interest for wastewater treatment, food packaging, and biomedical applications. This relates to the relatively high surface area and porosity of such fibrous chitosan materials that synergize with their unique physicochemical properties. Various methods are involved in the preparation of chitosan composite fibrous materials, which include the modification of the biopolymer that serve to alter the solubility of chitosan, along with post-treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 136 publications
(307 reference statements)
0
12
0
Order By: Relevance
“…In contrast with other study which presented chitosan hydrogel with rough surface but with no pores were observed on the surface [25]. This is due to the freeze-thawing method has been used to create porous chitosan hydrogel with interconnected pores [42]. During cooling the prepared chitosan hydrogel, the nucleation and the ice crystals was grown and moves into nonnucleated solution leading to change the morphology and form interconnected pores [46].…”
Section: Characterization Of Fcs Hydrogelmentioning
confidence: 83%
See 1 more Smart Citation
“…In contrast with other study which presented chitosan hydrogel with rough surface but with no pores were observed on the surface [25]. This is due to the freeze-thawing method has been used to create porous chitosan hydrogel with interconnected pores [42]. During cooling the prepared chitosan hydrogel, the nucleation and the ice crystals was grown and moves into nonnucleated solution leading to change the morphology and form interconnected pores [46].…”
Section: Characterization Of Fcs Hydrogelmentioning
confidence: 83%
“…Moreover, GO and CNT particles may be blocking the pores of chitosan hydrogel, which is impact on the diffusion of the pollutants through the porous structure and led to decrease the adsorption capacity [40]. Therefore, various researches have been used physical modi cations of hydrogels to control the porosity to form superporous structure with high swelling properties such as gas blowing or freeze drying techniques, which can increase its adsorption capacity [41][42][43]. The freeze-drying technique has its own disadvantage as well such as high energy required, time consuming and may led to shrinkage the network structure because the interfacial tension resulted by solvent evaporation thus limiting their usage [44,45].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2a highlights the main areas of research that have made a significant contribution to this field. The most promising method for obtaining biodegradable nanofibers is electrospinning from polymer solutions [3,4]. Electrospinning of nanofibers is possible from a solution of both natural polymers (collagen, gelatin, chitosan) and synthetic ones (PCL, polyethylene glycol, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Nanofibers obtained from natural polymers demonstrate high biocompatibility; however, obtaining stable and homogeneous nanofibers is a rather tricky task [5]. For a long time, it was almost impossible to obtain pure collagen and chitosan nanofibers and, therefore, fibers consisting of a mixture of polymers (for example, chitosan/polyethylene oxide) were obtained [3,4]. In addition, collagen is expensive, and collagen and gelatin nanofibers are often unstable in an aquatic environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation